1989
DOI: 10.1128/jvi.63.8.3362-3367.1989
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a simian virus 40 mutant T antigen substituted in the hydrophobic region: defective ATPase and oligomerization activities and altered phosphorylation accompany an inability to complex with cellular p53

Abstract: We have analyzed the biochemical properties of a nonviable simian virus 40 (SV40) mutant encoding a large T antigen (T) bearing an amino acid substitution (Pro-584-Leu) in its hydrophobic region. Mutant 5080 has an altered cell type specificity for transformation (transforming mouse C3H1OT1/2 but not rat REF52 cells), is defective for viral DNA replication, and encodes a T that is unable to form a complex with the cellular p53 protein (K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…However, this proved difficult because there was evidence that the removal of a hydrophobic region of the protein (residues 571 to 588) resulted in the loss of some activities, including complexing with the cellular protein p53 (41,68) and the transformation of rat REF52 cells (41). Furthermore, a single-amino-acid substitution at residue 584 (Pro to Leu) resulted in a similar loss (41,63). Consequently, we made several COOH-terminal deletions that did not affect this region as well as some that did.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this proved difficult because there was evidence that the removal of a hydrophobic region of the protein (residues 571 to 588) resulted in the loss of some activities, including complexing with the cellular protein p53 (41,68) and the transformation of rat REF52 cells (41). Furthermore, a single-amino-acid substitution at residue 584 (Pro to Leu) resulted in a similar loss (41,63). Consequently, we made several COOH-terminal deletions that did not affect this region as well as some that did.…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical properties of mutant Pro-584-Leu. A single point substitution mutant of T antigen (Pro-584 to Leu) has been previously described (41,63). This mutation results in the loss of a number of biochemical activities (41, 65), presumably because of a structural alteration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tevethia et al (62) have characterized a deletion mutant missing amino acids 587 to 589 which does not bind p53. Tack et al (61) have shown that, in fact, a base substitution mutation at amino acid 584 affects a number of functions of SV40 large T antigen, including the ability to hydrolyze ATP and to oligomerize. This suggests that the region of amino acids 570 to 588 may play a general structural role and is not necessarily contained within the domain of SV40 large T antigen which contacts p53.…”
Section: Discussionmentioning
confidence: 99%
“…We have been characterizing a collection of T-antigen mutants that carry amino acid substitutions, deletions, or insertions within the ATPase domain (19,44,54). This study reports the initial characterization of three mutant T antigens that FIG.…”
Section: Discussionmentioning
confidence: 99%